Improvement of Sensory Quality: Alteration of Physicochemical Characteristics and Antioxidant Activity of Immature Robusta Coffee Treated with Acetic Acid - Fitriani, Vita; Ningrum, Andriati; Setyaningsih, Widiastuti; Supriyadi, Supriyadi (Trends in Sciences, 2025)
Immature green coffee beans, which originate from green coffee cherries, are defective beans that are difficult to distinguish from mature green beans. Roasting these immature green beans produces quaker beans, which can reduce coffee quality. Acid treatment has been studied to improve the aroma quality of coffee. Acetic acid, an organic acid in coffee produced during fermentation and commonly used as vinegar, requires further study to determine its effects on immature coffee beans. This study investigated the effect of acetic acid treatment on the sensory, physicochemical and antioxidant properties of immature Robusta coffee beans. Immature green beans were soaked in acetic acid solutions of varying concentrations (0, 1, 2, and 3 %) and durations (30, 60, and 90 min) at 35 °C. Immature coffee beans had lighter brown color after roasted, and have higher chlorogenic acid (65.39 mg/g), caffeine (26.08 mg/g) and total soluble phenolic contents (65.70 mgGAE/g) than mature beans (p < 0.05). The roasted coffee of CI3-90 was the best acetic acid treatment sample with the highest cupping score (82.9) and the most intensely brown color, which resulted in decreased brightness (38.64 to 30.54) and yellowness (29.91 to 25.79). The acetic acid treatment significantly reduced total soluble phenolic content (61.58 to 45.26 mgGAE/g), chlorogenic acid content (20.10 to 14.64 mg/g) and trigonelline content (7.40 to 6.07 mg/g) of immature roasted coffee beans. Nevertheless, acetic acid treatment did not significantly influence caffeine content or antioxidant activity in either the green or roasted immature coffee beans (p > 0.05). HIGHLIGHTS Acetic acid treatment can improve the sensory and color quality of roasted immature coffee beans. Treating immature coffee beans with 3 % acetic acid for 90 min is the best treatment, resulting in the highest cupping score and roasted bean colors that are close to the roasted color of mature coffee beans. The chlorogenic acid and trigonelline concentrations in green and roasted immature coffee exhibited a tendency to decrease with increasing acetic acid concentrations and treatment durations. The antioxidant activities of immature green and roasted coffee beans remained relatively stable after acetic acid treatment. GRAPHICAL ABSTRACT